First Report of Nesting Habits, Nest Architecture and Foraging Behaviour of the Stingless bee, Tetragonula (Tetragonula) ruficornis (Smith) (Hymenoptera: Apidae: Meliponini) from India - Hadimani, Basavaraj N.; K. M., Kumaranag; Dey, Debjani (Sociobiology, 2024)
The present study aimed to understand nesting habits, nest architecture, and foraging behavior of the stingless bee, Tetragonula (Tetragonula) ruficornis Smith, a widespread species in the north Indian plains from Varanasi to Punjab. Among the 47 wild, unmanaged colonies studied, 27 were situated in the cavities of tree trunks and 20 in the cavities of building walls. The internal nest structure revealed that brood cells were arranged in clusters at the center of the cavity with encircling pollen and honey pots. Further, the natural nesting cavity’s total length, width, and height varied from 105 to 168 mm, 129 to 216 mm, and 283 to 472 mm, respectively. The foraging activity of outgoing and incoming foragers of T. ruficornis varied significantly during different hours of the day, across the seasons and prevailing weather conditions. Further, activity was limited to daytime from 08:00 to 18:00 h, with peak activity of outgoing and incoming forager bees between 10:00 and 12:00 h during all seasons. Irrespective of seasons, the foraging activity of outgoing, pollen, and nectar foragers was at its maximum at 12:00 h. However, foraging ceased during December and January due to low temperatures, while peak activity was observed during April. The foraging pattern showed a significant positive correlation with mean monthly maximum and minimum temperatures and a significant negative correlation with relative humidity. The current investigation delivers crucial information on nest architecture and foraging behavior, which could be exploited for designing bee hives and utilization in directed pollination services.